VALIDATION OF THE INSTRUMENTS OF LEARNING READINESS WITH E-LEARNING USING RASCH MODELING TO EMPOWER TECHNOLOGICAL CONTENT KNOWLEDGE (TCK) - Mobinta Kusuma; Purwo Susongko; Yuni Arfiani (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2019)
E-learning based learning is a trend in era 4.0 that requires learning readiness. This study is aimed at (1) developing GS-based e-learning readiness scale items to empower standardized TCKs; (2) validating the scale of e-learning readiness using Rasch modeling. The method used is the research on the development of modified Plomps according to needs, consisting of 3 stages, namely (1) the initial investigation stage; (2) stages of development (scale design construction); and (3) assessment stages (tests, evaluations and revisions). ata analysis using Rasch modeling with R-program 3.1.2. The results showed that the preparation of standardized e-learning learning readiness scale items through (a) study of the learning readiness scale theory; (b) defining concepts and operations; (c) determine dimensions; (d) determine indicators; (e) compile scale items; (f) rational validation by experts; (g) field trials; (h) Rasch modeling validation test. Validation of rasch modeling shows that e-learning readiness scale items are declared valid by considering aspects of content and substance. Therefore, this instrument can be applied in learning